Assessment of knowledge, attitude and practice of rabies prophylaxis among medical officers of anti-rabies vaccination clinics of Municipal Corporation of Greater Mumbai - Pasi, Achhelal R.; Sudarshan, M. K.; Kaushal, Kanica; Dikid, Tanzin; Jagtap, Sheela; Rathod, R. S.; Aroskar, Khyati; Gaikwad, Pragati B. (International Journal Of Community Medicine And Public Health, 2021)
Background: We conducted the present study to assess the knowledge, attitude and practice of rabies prophylaxis among medical officers of anti-rabies vaccination clinics of Municipal Corporation of Greater Mumbai (MCGM). Methods: We conducted a cross sectional study in 30 ARV clinics of MCGM. We collected data using pretested, structured, self-administered questionnaire and a facility survey check list. Questionnaire included questions pertaining to epidemiology of animal bite, biologicals supplied, protocols and guidelines for rabies prophylaxis, dosage and route of administration of ARV and training status. We analysed data using Microsoft Excel, 2007. Spearman’s rank correlation and Friedman test was used to examine the relationship between knowledge, attitude, and practice. The results were presented in the form of rates and ratios appropriately and p≤0.05 was considered statistically significant. Results: Mean knowledge, attitude and practice score of the study participants was 74.6%, 68.7% and 41% respectively. The difference between knowledge, attitude and practice was statistically significant (p<0.01). Knowledge poorly correlated with attitude (r=0.18) and practice (r=0.13). Conclusions: In Mumbai ARV clinics are uniformly spread in the community. All the clinics are well equipped and staffed. There was no shortage of vaccine in any centre. Counselling of patients was done in all ARV clinics however there was lack of patient education materials. Knowledge of medical officers in respect of dose, route of administration, site of vaccination and schedule of vaccination of anti-rabies vaccine was good. The knowledge of immunoglobulins was poor. Knowledge poorly correlated with attitude and practice.